Representation of the Diurnal Distribution of Organic Aerosol by Multidimensional Liquid Chromatography Systems - FLORES RANGEL, ROSA MARIA (My University, 2021)
Aerosols have various effects on human health, climate, and ecosystems. Aerosols also have an important role in climate changeby altering the radiation balance and lifetime and properties of clouds. Organic aerosol (OA) is composed of a mixture ofhundreds to thousands of organic compounds that varies geographically, diurnally, and seasonally according to several factors,such as type and concentration of precursor, type and concentration of oxidants, temperature, relative humidity, among others.The type and number of functional groups composing individual organic species influence their interaction with water vaporand sunlight, therefore affecting both the water cycle and radiation balance. Great efforts have been made to develop analyticaltechniques that allow the identification and quantification of individual species composing this complex mixture of organicmatter and decrease the uncertainty of models to accurately predict OA formation and evolution. In this study, it was foundthat most of the column combinations were not adequate and the best system was provided by methanol: water (1:1). Thecombination of columns that provided the best separation of the standard compounds was provided by Cyclohexyl and Methylas primary and secondary columns. However, when this combination of columns was used to represent the evolution of ambientair organic aerosols, significant co-elution was observed. The positive outcome of this study will be helpful to evaluate 2D-LCas a potential technique for more accurate determination of organic aerosol components and to understand organic aerosolformation and transformation pathways that can be used in secondary organic aerosol production models.

Aerosollerin; insan sağlığı, iklim ve ekosistemler üzerindeki çeşitli etkileri vardır. Ayrıca, aerosoller radyasyon dengesini ve_x000D_ bulutların ömür ve özelliklerini değiştirerek iklim değişikliğinde de önemli rol oynamaktadır. Organik aerosoller (OA),_x000D_ yüzlerce ve binlerce değişik bileşikten oluşurlar ve bu bileşikler coğrafik, gün ve mevsime göre oksidan konsantrasyonu ve_x000D_ türü, sıcaklık, bağıl nem gibi bir dizi faktöre bağlı olarak değişiklik gösterirler. Özgün organik türleri oluşturan fonksiyonel_x000D_ grupların sayısı ve tipi, aerosollerin su buharı ve güneş ışığı ile olan etkileşimini belirler ve bu nedenle su çevrimi ve radyasyon_x000D_ dengesini etkiler. Karmaşık bir karışım olan bu organik maddenin hangi türlerden oluştuğu ve bunların miktarının belirlenmesi_x000D_ ile OA üretimi ve gelişimini tahmin eden modellerdeki belirsizliğin azaltılması konularında büyük çabalar harcanmıştır. Bu_x000D_ çalışmada, kolon kombinasyonlarının çoğunun yeterli olmadığı ve en iyi sistemin metanol: su (1:1) ile sağlandığı bulundu._x000D_ Standart bileşiklerin en iyi ayrışmasını sağlayan sütunların kombinasyonu, birincil ve ikincil sütunlar olarak Sikloheksil ve_x000D_ Metil ile sağlandı. Bununla birlikte, bu sütun kombinasyonu, ortam havası organik aerosollerinin gelişimini temsil etmek için_x000D_ kullanıldığında, bileşiklerin kolonlarda istenilen düzeyde ayrışmadığı gözlemlenmiştir. Bu çalışmanın çıktıları, 2D-LC_x000D_ yönteminin organik aerosol bileşenlerin daha doğru tespiti için potansiyel bir teknik olarak değerlendirilmesine ve ikincil_x000D_ organik aerosol üretim modellerinde kullanılan organik aerosol oluşumu ve dönüşüm yollarını anlamaya yardımcı olacaktır._x000D_ Anahtar Kelimeler: çok boyutlu sıvı kromatografi, 2D-LC, organik aerosol, sık aralıklı toplanmış örnekler._x000D_
Organik Aerosolün Çok Boyutlu Sıvı Kromatografi Sistemleri ile Günlük Dağılımının Gösterimi